Implementation of Game-Based Learning (GBL) with Kahoot! in Encouraging Active Learning on Statistics - Pardede, Ayu Agustina; Listiani, Tanti (Universitas Wiralodra, 2024)
Good understanding is a fundamental aspect of learning, and it involves the active participation of students. In one school in Karawaci, there were problems with learning activities, such as sleepy students who focused on devices, tended to ask or answer passively, and did not do assignments or discuss. In response to this, teachers play a role in presenting learning that helps students, namely through varied and exciting teaching by implementing Game-Based Learning (GBL) assisted by Kahoot! This study aimed to show the extent to which Kahoot-assisted GBL! Can encourage active learning and describe its application in encouraging active learning in statistical material. The research method used is descriptive qualitative. The results showed an increase in learning activity after the implementation of Kahoot!-assisted GBL, from 42.4% to 71.3%. This success is supported by motivation, appreciation, reprimand, and interaction that creates a comfortable atmosphere for students. Suggestions for future research include repeating the application of Kahoot!-assisted GBL, exploring the use of other games and applying them to different grade levels